Simplifique as expressões:
A-(2x+1)²+(3x+1)²
B-5x-(2x+3)²
C-(x+5)²-x(x+3)
Calcule:
A-(m-
)²
B-(
-1)²
Soluções para a tarefa
Respondido por
15
a)
(2x+1)²+(3x+1)²=
4x²+4x+1+9x²+6x+1=
13x²+10x+2
b)
5x-(2x+3)²=
5x-(4x²+12x+9_=
5x-4x²-12x-9=
-4x²-7x-9
c)
(x+5)²-x(x+3)=
x²+10x+25-x²-3x=
7x+25
![(m- \frac{1}{2} )^2=m^2-m+ \frac{1}{4} (m- \frac{1}{2} )^2=m^2-m+ \frac{1}{4}](https://tex.z-dn.net/?f=%28m-+%5Cfrac%7B1%7D%7B2%7D+%29%5E2%3Dm%5E2-m%2B+%5Cfrac%7B1%7D%7B4%7D+)
![( \frac{a}{2} -1)^2= \frac{a^2}{4} -a+1 ( \frac{a}{2} -1)^2= \frac{a^2}{4} -a+1](https://tex.z-dn.net/?f=%28+%5Cfrac%7Ba%7D%7B2%7D+-1%29%5E2%3D+%5Cfrac%7Ba%5E2%7D%7B4%7D+-a%2B1)
(2x+1)²+(3x+1)²=
4x²+4x+1+9x²+6x+1=
13x²+10x+2
b)
5x-(2x+3)²=
5x-(4x²+12x+9_=
5x-4x²-12x-9=
-4x²-7x-9
c)
(x+5)²-x(x+3)=
x²+10x+25-x²-3x=
7x+25
Usuário anônimo:
A melhor Ismen você é realmente um gênio que Deus te ilumine
Perguntas interessantes